A-sides a cosmology of audio editions by artists around the "Arc Lémanique" region - Schmid, Laurent 1960-; Bovet, Roxane; Armleder, John M. 1948- (HEAD, 2020)
Une anthologie analytique des disques d'artistes en Suisse
Keywords: Geschichte 1975-2019; Schallaufzeichnung; Klangkunst; Künstler; Genfer See -- Region; Aufsatzsammlung; Interview